COUNT DRACULA, LOUIS DE POINTE DU LAC AND EDWARD CULLEN: THE ARCHETYPAL SHIFT OF VAMPIRES FIGURES ACROSS THREE ERAS OF ENGLISH LITERATURE - Setiyawati, Bety (CrossOver, 2024)
The research aims at finding out the archetype, archetypal shift and the dominant archetype of vampire figures: Count Dracula, Louis de Pointe du Lac and Edward Cullen. The methods used in this research is descriptive qualitative research, used documentation as the technique of collecting data. In this research, the researcher used Archetype theory by Margareth Mark and Carol Pearson and Linda Hutcheon’s theory of shifting to analyze the data. The result of this research showed that there were 137 data in total and are 10 of 12 total archetypes. The analysis on the archetypal shifting classified were; 8 archetypes uses historicizing and 129 dehistoricing.  15 archetyes uses racializing and 122 archetypes uses deracializing. 9 Disembodiments and 3 embodiments. It is found that each figure has a different orientation of characterization depicted its own zeitgeist.  Count Dracula a vampire from Victorian era has a clear characterization of a ruler. Contrastingly, Louis de Pointe du Lac of post-modern era has an ambigous personality of being good ‘evil’ and is bond through his past. Differently, A vampire of Contemporary era, Edwrad Cullen, has an obvious characterization as a lover with 2 dominant archetypes takes 66% of the data. Furthermore, the dominant archetype of the data is the Lover which takes 30% of the data as both Louis and Edward created in the era where there is no distinguish point of being good and evil. Keywords: Vampire, Archetype, Archetypal Shift, Characterization.